Decoding the Role of Glycans in Malaria - Gomes, Pollyanna S.; Feijó, Daniel F.; Morrot, Alexandre; Freire-de-Lima, Celio G. (Frontiers in Microbiology, 2017)
Complications arising from malaria are a concern for public health authorities worldwide, since the annual caseload in humans usually exceeds millions. Of more than 160 species of Plasmodium, only 4 infect humans, with the most severe cases ascribed to Plasmodium falciparum and the most prevalent to Plasmodium vivax. Over the past 70 years, since World War II, when the first antimalarial drugs were widely used, many efforts have been made to combat this disease, including vectorial control, new drug discoveries and genetic and molecular approaches. Molecular approaches, such as glycobiology, may lead to new therapeutic targets (both in the host and the parasites), since all interactions are mediated by carbohydrates or glycan moieties decorating both cellular surfaces from parasite and host cells. In this review, we address the carbohydrate-mediated glycobiology that directly affects Plasmodium survival or host resistance.